Investigation into early interneuron circuits of the mouse visual cortex - Ghezzi, F (2022)
GABAergic interneurons play critical roles during cortical development in mammals, by maintaining excitatory-inhibitory balance and controlling emergent activity. In the mouse barrel cortex (S1BF), somatostatin-expressing (SST+) interneurons establish early, transient synaptic connections with thalamo-recipient excitatory neurons in cortical layer (L)4, while they receive transient thalamic inputs. This immature feed-forward inhibitory motif by SST+ cells acts as a scaffold for the mature S1BF neuronal networks and regulates developmental plasticity mechanisms. Given this critical role, it is conceivable transient networks by SST+ interneurons are a general feature of the developing mammalian cortex; however, there is limited knowledge on early networks and functions of SST+ interneurons in other brain regions. To explore this issue, the current thesis explores the primary visual cortex (V1) of the mouse, to study the degree of similarity between GABAergic interneuron networks and functions across sensory areas over early postnatal development. In vitro electrophysiology and optical techniques were used to map input/output connectivity patterns of SST+ interneurons in V1 to show they are only engaged in feedback inhibitory motifs with local excitatory neurons. Differences at the neuronal network level between V1 and S1BF relates to distinct functions played by SST+ interneurons across the developing brain. In vivo electrophysiology, together with optogenetics and chemogenetics, revealed SST+ interneurons in V1 regulate spontaneous activity but have minor impacts on early sensory activity before the onset of active perception. Circuit mapping experiments onto L6 excitatory neurons extended the concept of different early GABAergic networks between V1 and S1BF to the output layer of the cerebral cortex. Although canonical cortical circuits permeate the adult mammalian cortex, their developmental trajectories differ between similar primary sensory areas. GABAergic interneurons have been associated with neurodevelopmental disorders; it is, hence, pivotal to consider their developmental networks and functions to gain an understanding of the mechanisms underlying these disorders.